The Influence of Digital Transformation and Work Environment on Employee Performance through Motivation as an Intervening Variable in the Human Resources Development and Personnel Agency (Lebak Regency, Serang City and Cilegon City) - Astuti, Dini Puzi; Wiguna, Wahyu; Suparmoko, Muhammad (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This research is motivated by the disparity in employee data at the BKPSDM of Lebak Regency, Serang City, and Cilegon City, which arose due to suboptimal digital transformation and a work environment that did not fully support employee performance improvement. This condition has implications for the hampered employee service process and weakened employee work motivation. The purpose of this study is to analyze the influence of digital transformation and the work environment on employee performance, with work motivation as a mediating variable. The research method uses a quantitative approach with a Partial Least Squares (PLS-SEM)-based structural equation analysis technique processed using SmartPLS 3 software. The study population was all 185 BKPSDM employees in the three regions, with a sample of 127 employees determined using the Yamane formula. The research instrument was compiled based on the indicators of each variable, then tested for validity and reliability before use. The results of the study indicate that digital transformation and the work environment have a significant effect on employee performance, but digital transformation is not proven to have a direct effect on motivation. Instead, motivation plays an important role as an intermediary variable that bridges the relationship between the work environment and employee performance. The discussion of these findings confirms that the success of civil servant performance is determined not only by the adoption of digital technology, but also by the quality of a supportive work environment and internally developed motivation. This demonstrates the importance of strategies to strengthen motivation, increase digital capacity, and create a conducive work climate to optimize employee performance. In conclusion, this study provides empirical evidence that digital transformation needs to be accompanied by improvements in the work environment and strengthened motivation as a comprehensive strategy to enhance BKPSDM employee performance.